2022
DOI: 10.4067/s0718-27242022000200049
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and barriers of university-industry cooperation: a comparison between Brazil and Ireland

Abstract: University-industry cooperation (UIC) is increasingly seen as an essential innovation strategy and technology transfer offices (TTOs) play an important role in this process but are still neglected by industries and researchers. Public policies have been developed worldwide since the Bay-dole act in 1980, but emerging countries still face difficulties in promoting UIC compared to developed countries. This article aims to highlight and compare the main motivations and barriers for UIC in Brazilian and Irish TTOs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Compared to other studies (López-Martínez et al, 2007;Boardman and Ponomariov, 2009;Giuliani et al, 2010;Morales, 2019;Cudic et al, 2021;Da Silva and Sartori, 2022), only López-Martínez et al (2007) and Morales (2019) applied instruments similar to the EA-COOPTEC to measure UIC from the researchers' perspective. However, López-Martínez et al (2007) reported no evidence of validity or reliability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to other studies (López-Martínez et al, 2007;Boardman and Ponomariov, 2009;Giuliani et al, 2010;Morales, 2019;Cudic et al, 2021;Da Silva and Sartori, 2022), only López-Martínez et al (2007) and Morales (2019) applied instruments similar to the EA-COOPTEC to measure UIC from the researchers' perspective. However, López-Martínez et al (2007) reported no evidence of validity or reliability.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently a variety of indicators to measure different types of UIC activities (Gardner et al, 2010;Seppo and Lilles, 2012). In particular, the measurement of perception of T-Rs to UIC is a little explored field, the closest studies are those of López-Martínez et al (2007), Boardman and Ponomariov (2009), Giuliani et al (2010), Cudic et al (2021), Da Silva andSartori (2022), andMorales (2019). Cudic et al (2021) measured UIC by constructing indicators based on data reported by different sources with the purpose of studying the relationship between predictors of UIC and its outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges and obstacles to research-industry cooperation have been broadly addressed in the literature, being well established that they arise from complexities inherent to R&D&I and the institutional and cultural differences of the stakeholders (Albats, Bogers & Podmetina, 2020;Salles-Filho et al, 2021), such as the limitations resulting from the administrative and managerial differences experienced (Salles-Filho et al, 2021;Silva & Sartori, 2022). However, studies on the operational dynamics of these cooperations, particularly the factors of microfoundations dimensions (i.e., individuals, procedures and structures) (Felin et al, 2012) that contribute to shaping the collective outcomes, are still scarce (Albats, Bogers & Podmetina, 2020;Adegbile, Sarpong & Kolade, 2021;Salles-Filho et al, 2021).…”
Section: Ros and Challenges To Cooperation From The Perspective Of Mi...mentioning
confidence: 99%
“…Although the research-industry relationship is a recurring theme in discussions and innovation policies in Brazil aimed at innovative productive development (Brito Cruz, 2019;Salles-Filho et al, 2021), market and institutional deficiencies are still considered obstacles to the establishment of a more effective cooperation (Fischer, Schaeffer & Phaiffer, 2018;Salles-Filho et al, 2021;Silva & Sartori, 2022). Some scholars (such as Oliveira and Bonacelli (2019), Ribeiro, Salles-Filho and Bin (2015), Ronsom and Amaral (2017)) argue that the institutional strengthening of Brazilian ROs through the improvement of routines and collective capacities in research, development and innovation (R&D&I) is a mechanism for changes in the above scenario.…”
Section: Introductionmentioning
confidence: 99%